Room-temperature growth of colloidal Bi2Te3 nanosheets - Sokolikova,MS; Sherrell,PC; Bemmer,VL; Mattevi,C (Chemical Communications, 2017)
In this work, we report the colloidal synthesis of Bi2Te3 nanosheets with controlled thickness, morphology and crystallinity at temperatures as low as 20 °C. Grown at room temperature, Bi2Te3 exhibits two-dimensional morphology with thickness of 4 nm and lateral size of 200 nm. Upon increasing the temperature to 170 °C, the nanosheets demonstrate increased thickness of 16 nm and lateral dimensions of 600 nm where polycrystalline nanosheets (20 °C) are replaced by single crystal platelets (170 °C). Rapid synthesis of the material at moderately low temperatures with controllable morphology, crystallinity and consequently electrical and thermal properties can pave the way toward its large-scale production for practical applications.